Atividade física para promoção da saúde de idosos com doença de Alzheimer e seus cuidadores - Garuffi, Marcelo [UNESP]; Gobbi, Sebastião [UNESP]; Hernandez, Salma Stéphany Soleman [UNESP]; Vital, Thays Martins [UNESP]; Stein, Angelica Miki [UNESP]; Pedroso, Renata Valle [UNESP]; Corazza, Danilla Icasatti [UNESP]; Andrade, Larissa Pires de [UNESP]; Andreatto, Carla Andreza Almeida [UNESP]; Costa, José Luiz Riani [UNESP]; Stella, Florindo [UNESP] (My University, 2011)
Due to increased life expectancy worldwide is increasing the number of elderly with dementia, the most frequent being Alzheimer’s dementia, a progressive and neurodegenerative disease. "The Cinesioterapy Cognitive and Functional Program in elderly with Alzheimer’s Disease" (PRO-CDA) looking for, through the practice of physical activity, to intervene in symptoms of progressive disease, providing over all promotion of health for elderly and their caregivers. Through the work of multidisciplinary team, with health professionals and trainees from undergraduate courses, the project develops activities to benefit the participants, events for public awareness about the disease and improvement of professional and student health. So, the PRO-CDA hopes to contribute for improved quality of life, both of patients as the caregivers, as well contributing to the training of students and graduates in various areas of health.

Devido ao aumento da expectativa de vida mundial é cada vez maior o número de idosos com Demências, sendo a mais frequente a Demência de Alzheimer, uma doença neurodegenerativa e progressiva. O “Programa de Cinesioterapia Funcional e Cognitiva em Idosos com Doença de Alzheimer” (PRO-CDA) procura, através da prática de Atividade Física, interferir nos sintomas progressivos da doença, proporcionando, sobretudo a promoção de saúde para idosos e seus cuidadores. Por meio do trabalho de uma equipe multiprofissional, com profissionais de saúde e estagiários de cursos de graduação, o projeto desenvolve atividades para benefício dos participantes, eventos para conscientização da população a respeito da doença e aprimoramento de profissionais e estudantes da área da saúde. Assim, o PRO-CDA espera contribuir com melhora da qualidade de vida, tanto do paciente como do cuidador, além de contribuir com a formação profissional de estudantes e graduados nas mais diversas áreas da saúde.
Physical activity for health promotion in elderly with Alzheimer’s disease and their caregivers
Keywords: Alzheimer disease; Physical activity; Aging; Health promotion; Doença de Alzheimer; Atividade física; Envelhecimento; Promoção de saúde